Self-Triggering Based on Lyapunov with Adaptive Control Law for WNCS - Pecker Marcosig, Ezequiel (2014)
This paper addresses the use of Lyapunov functions to self-triggering control implementation. In order to do this a condition, which comes from a sampling technique named Lyapunov sampling, is proposed. The results show the average sampling frequency reduction that can be assessed with this self-triggering method with respect to event and periodic sampling schemes. Using this to dynamically adjust sampling-time, a Lie-algebraic approach is considered to guaranteed closed-loop stability and performance. These results are particularly useful for wireless networked control systems.